Risk factors for venous thromboembolism (VTE) after adrenalectomy for adrenal cortical neoplasms. Issue 7 (23rd August 2022) - Moore, Maureen D.; Agrusa, Christopher; Ullmann, Timothy M.; Beninato, Toni; Zarnegar, Rasa; Fahey, Thomas J.; Finnerty, Brendan M.
Abstract: Background: Incidence of venous thromboembolism (VTE) after adrenalectomy for adrenal cortical carcinoma (ACC) is unknown. Herein, we aim to identify the relative incidence and risk factors of VTE after adrenalectomy for ACC. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried to identify patients who underwent adrenalectomy for ACC, Cushing syndrome (CS), and benign adrenal cortical syndromes (BACS). Univariable and multivariable analyses were used to determine clinical characteristics, 30‐day postoperative VTE occurrences, and associated risk factors. Khorana oncologic risk score (KRS) for VTE was calculated and compared between groups. Results: A total of 5896 patients were analyzed: 576 ACC, 371 CS, and 4949 BACS. Postoperative VTE occurred 0.9%, with the highest rate occurring in ACC (2.6% ACC vs. 1.6% CS vs. 0.7% BACS, p  < 0.001). Forty percent of VTEs in the ACC cohort were diagnosed postdischarge. ACC patients with KRS ≥ 2 had a 9.6% incidence of VTE ( p  = 0.007). Multivariable analysis identified increased age ( p  = 0.03), presence of adrenal cancer ( p  = 0.01), and KRS ≥ 2 ( p  = 0.005) as risk factors for VTE after adrenalectomy. Conclusions: Postoperative VTE after adrenalectomy occurs most frequently for ACC. ACC patients with increased age and/or Khorana score ≥2 should be considered for extended VTE prophylaxis.